A callus transformation system for gene functional studies in soybean - Kun XU; Xiao-mei ZHANG; Cheng-ming FAN; Fu-lu CHEN; Jin-long ZHU; Shi-long ZHANG; Qing-shan CHEN; Yong-fu FU (Journal of Integrative Agriculture)
Obtaining transgenic plants is a common method for analyzing gene function. Unfortunately, stable genetic transformation is difficult to achieve, especially for plants (e.g., soybean), which are recalcitrant to genetic transformation. Transient expression systems, such as Arabidopsis protoplast, Nicotiana leaves, and onion bulb leaves are widely used for gene functional studies. A simple method for obtaining transgenic soybean callus tissues was reported recently. We extend this system with simplified culture conditions to gene functional studies, including promoter analysis, expression and subcellular localization of the target protein, and protein-protein interaction. We also evaluate the plasticity of this system with soybean varieties, different vector constructs, and various Agrobacterium strains. The results indicated that the callus transformation system is efficient and adaptable for gene functional investigation in soybean genotype-, vector-, and Agrobacterium strain-independent modes. We demonstrated an easy set-up and practical homologous strategy for soybean gene functional studies.